Antibiotics And Bacterial Resistance: A Global Challenge That Needs To Be Addressed - Sugiah, Sugiah; Fadli, Fadli; Hariati , Fitria; Cendekiawan, Khrisna Agung (Pt. Anagata Sembagi Education, 2025)
This study aims to explore the global challenges faced in addressing bacterial resistance to antibiotics, which are now one of the most serious health threats in the world. This study was conducted through the Systematic Literature Review (SLR) method by searching scientific articles from various databases such as PubMed, Scopus, and Google Scholar using the keywords